2019
DOI: 10.1007/s00606-019-01568-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sample age and taxonomic origin on the success rate of DNA barcoding when using herbarium material

Abstract: We have produced DNA barcodes for Finnish plant taxa. In this study, we specifically report the barcoding success for herbarium materials varying widely in age, also paying attention on success rate variation and genetic distances among different plant families. Additionally, we investigated whether the level of intraspecific variation differs between native and introduced species. The specimens had been collected between years 1867 and 2013. Among all studied specimens, the average success rates for any barco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Also for capture probes, the target enrichment efficiency declines with age [53]. This is in contrast to what has been observed for Sanger sequencing [35,54]. Similarly, while we in an earlier Sanger sequencing study observed that specimens collected later in the growing season had poorer success rate (boldsystems.org, project NNOR, n = 1805), time of season caused no problem for genome skimming.…”
Section: Effect Of Age and Time Of Seasonmentioning
confidence: 56%
“…Also for capture probes, the target enrichment efficiency declines with age [53]. This is in contrast to what has been observed for Sanger sequencing [35,54]. Similarly, while we in an earlier Sanger sequencing study observed that specimens collected later in the growing season had poorer success rate (boldsystems.org, project NNOR, n = 1805), time of season caused no problem for genome skimming.…”
Section: Effect Of Age and Time Of Seasonmentioning
confidence: 56%
“…Despite initial skepticism from national funding agencies, FinBOL has delivered primary research results of the very type traditionally supported by them. Deliverables to date include insights into the protein structure of the barcode region (Pentinsaari et al, 2016), species interactions (Kaartinen et al, 2010; Mutanen, Ovaskainen, et al, 2020; Nyman et al, 2015; Rytkönen et al, 2019; Vesterinen et al, 2013, 2016), taxonomy (Boonstra et al, 2018; Haarto & Ståhls, 2014; Hausmann et al, 2013; Huemer et al, 2020; Huemer & Mutanen, 2015; Ivanov et al, 2018; Kirichenko et al, 2016; Kozlov et al, 2017; Landry et al, 2013; Landvik et al, 2013; Lee et al, 2020; Liston et al, 2019; Mutanen, Aarvik, Huemer, et al, 2012; Mutanen et al, 2012, 2013, 2015, 2016, 2020; Nieminen et al, 2018; Pentinsaari et al, 2014; Pentinsaari et al, 2014; Pilipenko et al, 2012; Pohjoismäki & Haarto, 2015; Pohjoismäki et al, 2016; Prous et al, 2016, 2020; Pykälä & Myllys, 2016; Salmela et al, 2014; Sihvonen et al, 2020; Ståhls et al, 2015; Tabell et al, 2019; van Nieukerken et al, 2012; Wikström et al, 2020; Wilson et al, 2011), phylogenetics (Heikkilä et al, 2014; Kaila et al, 2020; Karsholt et al, 2013), faunistics (Korpelainen & Pietiläinen, 2017; Paukkunen & Kozlov, 2015), biogeography (Huemer et al, 2014, 2018; Mutanen, Hausmann, et al, 2012; Salmela, 2012), methodology (Kekkonen et al, 2015; Korpelainen & Pietiläinen, 2...…”
Section: Discussionmentioning
confidence: 99%